Нові адвентивні види флори України — Tulipa sylvestris L. (Liliaceae) та Rubus laciniatus Willd. (Rosaceae) - Мельник, В.І.; Гончаренко, В.І.; Савчук, Р.І. (Український ботанічний журнал, 2013)
На Полесье выявлены новые для флоры Украины адвентивные виды Tulipa sylvestris L. (Liliaceae) и Rubus laсiniatus Willd.
(Rosaceae), описаны условия их местообитаний и современное состояние популяций. New alien species for the flora of Ukraine, Tulipa sylvestris L.
(Liliaceae) and Rubus laciniatus Willd. (Rosaceae), were found in
Polissya. Their habitats and current state of populations are described.